The synthesis of the Gospel and life as a goal of evangelization - Stanisław Dyk (Polonia Sacra)
The article presents selected examples of the synthesis of the Gospel and life, which is the goal of contemporary evangelization. In implementing the prophetic purpose, it was emphasized that the proclamation of the Word of God is to illuminate and transform human existence. In implementing the priestly function, the focus was on celebrating the Eucharist, revealing it as a source of human strength and energy, a school of sacramental perception of life and appreciation of matter, as well as a space for forming a new man. In the implementation of the priestly function, however, attention was paid to the presence of the Church in the world and the Christian lifestyle, which is closely related to the promotion of man and the quality of his life. The study emphasizes that the existential orientation of evangelization establishes the proper relationship of the Church with the world. It involves accepting the world, dialogue with it, and transforming it in the spirit of the Gospel.